Theory of nuclear excitation by electron capture for heavy ions - Gagyi-Palffy, Adriana; Justus Liebig University Giessen (My University, 2006)
The resonant process of nuclear excitation by electron capture (NEEC) in collisions involving highly-charged ions has been investigated theoretically. NEEC is a rare recombination process in which a free electron is captured into a bound shell of an ion with the simultaneous excitation of the nucleus. Total cross sections for NEEC followed by the radiative decay of the excited nucleus are presented for various collision systems. The possibility to observe the NEEC in scattering experiments with trapped or stored ions was discussed focusing on the cases with the largest calculated resonance strength. As the photons emitted in different channels of the electron recombination process are indistinguishable in the total cross section, the interference between NEEC followed by the radiative decay of the nucleus and radiative recombination was investigated. The angular distribution of the emitted photons in the recombination process provides means to discern the two processes. Angular differential cross sections for the emitted photons in the case of E2 nuclear transitions were presented for several heavy elements.
Theorie der Kernanregung durch Elektroneneinfang bei schweren Ionen
Keywords: Elektronenrekombination; Kernanregung; hochgeladende Ionen; electron recombination nuclear excitation; highly-charged ions; ddc:530